MORPHOLOGY AND HISTOLOGY OF THE FEMALE SEX PHEROMONE - GLAND OF EPHESTIA CAUTELLA WIk. (LEPIDOPTERA : NOCTUIDAE), A SERIOUS PEST OF STORED GRAINS - SETHI, R. K.; JAIN, O.P.; GUPTA, B. D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The sex pheromone gland of female Ephesia cautella Wik is a glandular fold of ventral inter-segmental membrane of 8th and 9th abdominal segments. The epithelial cello are columnar, well-developed and are based on a thin basement membrane. The epicuticle is thin, it is having hollow-based spikes all along its outer surface. The endocuticle is quite thick, situated below the epicuticle and above the columnar cells. Nuceli are well-developed and basally placed, vacuoles are found in the SPG of the Pre-copulatory virgin female. The SPG of E cautella in its location and structure is closely related with that of the Amphipyrinae (Noctuidae).